Electrode life of aluminium resistance spot welding in automotive applications: a survey. (2nd January 2017) - Zhang, W. J.; Cross, I.; Feldman, P.; Rama, S.; Norman, S.; Del Duca, M.
Abstract : Short electrode life has been one of the crucial issues for aluminium resistance spot welding in high-volume automobile manufacturing. A fair amount of heat may be generated at the electrode/workpiece interface because of the high electrical contact resistance of the aluminium oxide layers. Correspondingly, rapid electrode degradation is observed due to severe Cu–Al alloying, pitting and cavity during welding. This issue has not yet been fully addressed. This survey focuses on the current studies of understanding and development of electrode life improvement specifically on those that extend electrode life via optimising the electrical contact resistance at the interface, including altering the surface conditions of the workpiece, weld parameters development and weld equipment selections, and new electrode designs, and etc.